The Influence of Customer Reviews, Ratings and Brand Image on Purchase Interest in Tiktokshop Indonesia - Faradissa, Silsiyah; Hapsari, Radhita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The objective of this research is to corroborates the effects of customer review, rating, and brand image on consumers’ intention to purchase Daviena, a skincare brand, via TikTok Shop in Indonesia. A number of 194 people with the minimum age of seventeen years who have TikTok in their smartphones, who have ever made purchases via TikTok Shop, and who know about the products of Daviena were selected as the respondents. Having been assessed using validity, reliability, and classical assumption tests, the data was analyzed through multiple linear regression. This study finds that customer review positively and significantly influences the purchase intention, that rating positively and significantly affects the purchase intention, and that brand image positively and significantly impacts the purchase intention. Further, the results of the analysis also demonstrate that customer review, rating, and brand image simultaneously have positive and significant impacts on the purchase intention.